Description of flecainide usage from 2005-2018 in the Danish population. (19th May 2022) - Krogager, E; Lock-Hansen, M; Vibe-Rasmussen, P; Dalgaard, F; Ruwald, M; Zoner, C; Toennesen, J; Schjerning, AM; Gislason, G; Pallisgaard, JL
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Flecainide is an antiarrhythmic class 1C agent used to treat cardiac arrhythmias. Due to the risk of pro-arrhythmia and 1:1 conduction with flecainide, concomitant treatment with atrioventricular nodal blocking (AVNB) agents is advised. However, little data exist pertaining to the real-world use of flecainide and concomitant AVNB therapy. Purpose: We sought to investigate the change over time in the use of flecainide and AVNB agents in relation to patient characteristics. Methods: Using the Nationwide Danish registers, all Danish patients above 18 years with a redeemed prescription for flecainide between January 1st, 2005, and December 31st, 2018, and included at the date of the first prescription. The use of AVNB agents was identified in the period from 180 days prior to and 180 days after the inclusion date. Individual AVNB agents were divided into beta-blockers, class IV calcium channel blockers, and digoxin. Results: The study cohort consisted of 6, 594 patients with a median [IQR] age increasing from 59 [53-65] years in 2005 to 63 [56-69] in 2018, 59 % were men, and the most frequent arrhythmia diagnosis was AF (90.1%). In total, there were 297 patients starting flecainide in 2005 and 491 in 2018, with the highest number of patients in 2011, with 613 new users (Figure 1). Compared to the 144, 215 patients with prevalent atrial fibrillation in Denmark in 2018, the number of patients using flecainide was only 0.3% this year. The percentage of patients on concomitant AVNB treatment was high throughout the study period, with 93% in 2005 and 95% in 2018, giving an average increase of 0.3% per year over time. The most frequently used AVNB was beta-blockers, and the least frequently used were the class IV calcium channel blockers. (Figure 2) Over time, the number of patients with concomitant AVNB treatment to flecainide decreased from 94% the first year in flecainide treatment to 90% between the second and third years. Between the firth and sixth year in flecainide treatment, the number was down to 86%. The number of patients with a diagnosis of ischemic heart disease was 10% in 2005, dropping to 6% in 2018 Conclusions: Flecainide use increased from 2005 to 2018. The use of AVNB was high in patients prescribed with flecainide and increased over time, with beta-blocker as the most frequent.